A Study on the Influence of the Forming Strategy on the Main Strains, Thickness Reduction, and Forces in a Single Point Incremental Forming Process - Adrian Blaga; Valentin Oleksik (Advances in Materials Science and Engineering)
This paper comprises an experimental study for a complex geometry part obtained by incremental forming. Due to the process complexity (the presence of forces on three directions—a vertical one and two in the blank's plane), a three axes CNC milling machine, capable of describing the complex paths covered by the punch for obtaining the truncated cone-shaped parts, has been chosen. To obtain a truncated cone, three different trajectories were selected: in first and second variants after each vertical press having a constant step, the punch covers a circular path. The differences show that the following circular trajectory can start at the same point or can be shifted at an angle of 90° from the previous press point. In the last variant, the punch performs a spatial spiral trajectory. The main objective of our study was to determine the optimal forming strategy, by shifting the press position of the punch and the path it follows to obtain a truncated cone through single point incremental forming. Thus, the strain distribution can be homogeneous, and the thickness reduction and the process forces are minimal.